Paragenesis And Metal Associations - In Interior Alaska Gold Deposits: An Example From The Fairbanks District - K. Severin; P. Marion; B. Flanigan (Society for Mining, Metallurgy & Exploration, 2003)
"Plutonic-related" gold deposits in Interior and SW Alaska (Tintina Gold Belt) vary significantly in size, grade, vein/deposit morphology, depth of emplacement, distance from causative pluton and metal association. Metal associations such as Au-Bi and Au-As- (Sb-Hg) are a good empirical indicator of the depth of emplacement and distance from causative pluton. These associations have been used successfully in exploration. Results from several analytical techniques also suggest a phenomenological cause for these metal associations. Gold and bismuth have paired mineralogy at high temperatures and, thus, are best correlated at deposits that are deep and/or close to causative intrusions.